Hypophosphataemia is common in patients with aneurysmal subarachnoid haemorrhage. Issue 10 (6th September 2021) - Erritzøe‐Jervild, Mai; Wesierski, Jesper; Romano, Stefano; Frikke‐Schmidt, Ruth; Orre, Matias; Eskesen, Vagn; Olsen, Markus H.; Møller, Kirsten
Abstract: Introduction: Hypophosphataemia is common in critically ill patients, but neither its prevalence nor its association with outcome have been investigated specifically in patients with aneurysmal subarachnoid haemorrhage (aSAH). Methods: Patients with aSAH and at least one phosphate measurement were included from two independent cohorts; an American cohort extracted from two open‐access databases (Medical Information Mart for Intensive Care‐III and eICU Collaborative Research Database v. 2.0) and a Danish cohort consisting of patients with aSAH admitted to Rigshospitalet, Denmark over a 4‐year period. In each cohort, we calculated the prevalence of mild (0.32–0.80 mmol/L) and severe (<0.32 mmol/L) hypophosphataemia and their association with in‐hospital mortality before and after propensity‐score matching. Results: Hypophosphataemia occurred in 72.4% (95% CI: 68.1–76.3) of patients in the American cohort ( n = 471) and 54.9% (50.0–59.7) in the Danish cohort ( n = 419). However, it was not associated with mortality in neither full (American: Mild, Odds ratio (OR) 0.99 (0.91–1.07), Severe OR 1.20 (0.95–1.51); Danish: Mild, OR 1.01 (0.95–1.08), Severe OR 1.20 (0.95–1.51)) nor propensity‐score matched cohorts (American ( n = 168): Mild, OR 1.06 (0.88–1.28), Severe OR 1.46 (0.96–2.12); Danish ( n = 44): Mild, OR 1.16 (0.82–1.65), Severe OR 0.45 (0.13–1.55)). Conclusion: In this retrospective study of patients with aSAH, hypophosphataemia was common.